Inflammation blood and tissue factors of plaque growth in an experimental model evidenced by a systems approach - Pelosi, Gualtiero; Rocchiccioli, Silvia; Cecchettini, Antonella; Viglione, Federica; Puntoni, Mariarita; Parodi, Oberdan; Capobianco, Enrico; Trivella, Maria Giovanna (Frontiers in Genetics, 2014)
Purpose.The multifactorial pathogenesis of coronary atherosclerotic lesion formation has been investigated in a swine model of high cholesterol diet induced atherogenesis and data processed by a systems approach. Methods. Farm pigs were fed on standard or high cholesterol diet of 8 and 16 weeks duration. Plasma assessment of total cholesterol, HDL ,LDL and ELISA of some cytokines and ICAM-1 were performed on baseline and end-diet samples. Segments of the right coronary artery were incubated for 24 hours in serum-free medium to collect secreted proteins and their expression analysed by mass spectrometry. Data of plasma and tissue factors were processed by a statistical systems inference approach : both histologic parameters of coronary intimal thickness (IT) and of lesion area (LA) were chosen as dependent variables (coronary atherosclerotic burden). Results. Relations among plasma adhesion molecules, cytokines, lipoproteins, tissue proteins and histology indexes were integrated in a model regression scheme. Bayesian Model Averaging (BMA) variable selection was chosen as a method to identify relevant factors associated to atherosclerotic burden: TNF was identified as an associated plasma marker, oxLDL and HDL as relevant lipoproteins; macrophage function related antioxidant Catalase enzyme, lysosome associated Cathepsin D, S100-A10, and Transforming growth factor-beta-induced protein ig-h3 were identified and selected as associated to atherogenesis outcome. Conclusions. The results of this systems approach are consistent with the hypothesis that, in high cholesterol diet-induced experimental atherogenesis, the interaction between plasma cytokines, lipoproteins and artery-specific proteins, influences lesion initiation and growth. In particular, some macrophage function related proteins are found significantly and positively associated to atherosclerotic burden, suggesting a novel molecular framework into the atherogenesis-inflammatory disorder.